Hydroxychloroquine: does prophylaxis work? - Jha, Atul; Bhartiya, Manish; Kumar, Vijay R.; Upreti, Vimal; Deshmukh, Parag; Dudani, Mayank; Chandru, Arjun; Singh, Dharambir (International Journal Of Community Medicine And Public Health, 2021)
Background: Healthcare workers are front line workers in management of SARS-CoV-2 pandemic. The higher risk of acquiring the infection due to increased contact and exposures has prompted multiple risk mitigation strategies. To assess the role of hydroxychloroquine pre-exposure prophylaxis in prevention of SARS-CoV-2 infection amongst HCWs.Methods: This retrospective cohort study assessed the effect of HCQS prophylaxis amongst HCWs in a tertiary care hospital in the north-eastern part of India. All HCWs, involved in management of SARS-CoV-2 were enrolled. The subjects were retrospectively divided in two groups on HCQ prophylaxis. Group I (51.8%, n=116) taking HCQ prophylaxis and group II (48.2%, n=108) not taking the prophylaxis. The demographic characteristics, use of PPE, HCQ prophylaxis and side effect profile were noted. Results: Of the whole cohort, 22.8% (n=51) subjects tested positive. In group I (n=116), 24 subjects (20.7%) tested positive, whereas in Group II (n=108), 27 subjects (25.0%) tested positive. Further analysis of the incidence of SARS-CoV-2 infection amongst the two groups demonstrated that the although the rate of infection was lower (20.7% vs 25%) in Group I as compared to group II [X2 (1, N=224)=0.371, p=0.5] but it was statistically insignificant.Conclusions: Our study involving HCWs, does not show a statistically significant reduction in the incidence of infection with pre-exposure prophylaxis. Based on our findings and published literature, a prophylaxis of HCQS against the SARS-CoV-2 infection cannot be recommended.